CURSES IN MACEDONIAN FOLKLORE PROSE (Philological Studies, 2023)
In Macedonian folklore, curses have an important place. They have been subject of review in different researches, where they are considered as simple forms and from different aspects. However the fact is that they are often found as an integral part both of legends and myths, as well as in folk tales, not only in dialogical forms but also in indirect speech. At the same time, it should be borne in mind that curses are a reflection of the folk psychology and the mentality of the people and appear as a driving force of the narrative. Therefore, the object of our interest are the syntactic peculiarities of curses in Macedonian folk tales, above all the most common structures in which the wish  of the participants in the communication is shown, which is most often expressed with a da-construction,  in the Macedonian language also known as: subjunctive, optative-subjunctive, conjunctive (Минова-Ѓуркова 2000: 75).